Molecular Imaging of IGF-1R in Cancer. (6th November 2017) - Sun, Yingying; Sun, Xilin; Shen, Baozhong
The important role of insulin-like growth factor 1 receptor (IGF-1R) in malignant tumors has been well established. Increased IGF-1R activity promotes cancer cell proliferation, migration, and invasion and is associated with tumor metastasis, treatment resistance, poor prognosis, and shortened survival in patients with cancer. However, while IGF-1R has become a promising target for cancer therapy, IGF-1R-targeted therapy is ineffective in unselected patients. It is therefore essential to evaluate IGF-1R expression before treatment in order to identify responsive patients, monitor therapy efficacy, and estimate prognosis. Insulin-like growth factor 1 receptor molecular imaging is an optimal method for assessing the expression of IGF-1R in vivo accurately and noninvasively. In this review, we will summarize the current status of IGF-1R molecular imaging in cancer, in which 5 major classes of ligands that have been developed for noninvasive IGF-1R molecular imaging will be discussed: natural ligands, monoclonal antibodies, antibody fragments, affibodies, and small molecules. For decades, IGF-1R molecular imaging is studied in full swing and more effort is needed in the future.